2010
DOI: 10.1007/s00296-010-1448-8
|View full text |Cite
|
Sign up to set email alerts
|

Programmed initiation of hemodialysis for systemic amyloidosis patients associated with rheumatoid arthritis

Abstract: Reactive amyloidosis is a serious systemic disease in rheumatoid arthritis (RA). Amyloid protein can be deposited in kidneys, heart or gastrointestinal tract leading to organ failure. Renal involvement is a well-known complication in amyloidosis as this may culminate in end-stage renal disease (ESRD). Hemodialysis (HD) is always considered the treatment of choice for such patients; however, the prognosis is usually poor due to a large number of sudden deaths immediately following HD therapy. To circumvent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Rheumatic disease such as rheumatoid arthritis, which may be observed in dialysis patients and which may be a joint pain source [24], was excluded in our cohort. Due to the groups' homogeneity we can exclude the role of the central venous catheter, known to be a potential source of inflammation [25], as a cause of differences in ferritin mean values in the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Rheumatic disease such as rheumatoid arthritis, which may be observed in dialysis patients and which may be a joint pain source [24], was excluded in our cohort. Due to the groups' homogeneity we can exclude the role of the central venous catheter, known to be a potential source of inflammation [25], as a cause of differences in ferritin mean values in the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, existing data on patient survival and graft prognosis do not provide conclusive results about whether renal plantation is suitable for patients with AA amyloidosis [101]. An alternative to transplantation is chronic dialysis, but experience with dialysis in patients with AA amyloidosis has not yet as been encouraging [102,103]. Peritoneal dialysis increases the susceptibility to infection and protein loss [104].…”
Section: End-stage Renal Disease Treatment In Aa Amyloidosis Secondarmentioning
confidence: 99%
“…However, whether it is calcium dyshomeostasis that provokes Aβ production and accumulation [101], or vice-versa [102], remains to be elucidated. Either way, in addition to the Aβ unbalance, increased levels of Ca 2+ promoted protein tau hyperphosphorylation [103]. It was also suggested that amyloid oligomers induce membrane permeabilization, leading to increased intracellular Ca 2+ concentration [104].…”
Section: Calcium Hypothesismentioning
confidence: 99%
“…However, existing data on patient survival and graft prognosis do not provide conclusive results about whether renal plantation is suitable for patients with AA amyloidosis [101]. An alternative to transplantation is chronic dialysis, but experience with dialysis in patients with AA amyloidosis has not yet as been encouraging [102,103]. Peritoneal dialysis increases the susceptibility to infection and protein loss [104].…”
Section: Biomarkers Predicting Effectiveness Of Treatment For Aa Amyloidosis Secondary To Ramentioning
confidence: 99%